Science and Technology Publications Associated with the University of Mysore: A Bibliometric Examination Using Web of Science Database - H. A., Satheesha; Chandrashekara, M (Access: An International Journal of Nepal Library Association, 2025)
UoM (University of Mysore) reputations are significantly influenced by their publications. This bibliometric analysis, using VOS viewer, compiles Web of Science-indexed papers from the University of Mysore (UoM), India. The number of publications from UoM has been steadily increasing. In terms of international collaboration, UoM has partnered most frequently with institutions in China and India. Among UoM-affiliated authors, the most prolific author has published 104 articles. Authors associated with UoM who co-authored with fewer than 25 others had the highest number of cited publications. Currently, antioxidant activity is a major research focus at UoM. With an impressive record of 5,127 publications and extensive international collaborations with 36 countries, UoM demonstrates a strong global research presence.